The Effect of the Type of Planting Media and The Addition of O2 Nanobubbles on the Growth of Dendrobium burana Green × Ong Ang Ai Boon Orchid Plantlets in Vitro - Purnamasari, Viska; Rahayu, Tintrim; Jayanti, Gatra Ervi; Agisimanto, Dita (Jurnal ILMU DASAR, 2024)
Dendrobium orchids come in a variety of colors, shapes, and beauty that are in great demand. The process of growing orchids requires special handling of an appropriate growing environment, such as proper planting media and nutrients that can stimulate orchid growth. This type of thin liquid film media is the use of liquid media with an immersion system while vermiculite and perlite media have almost the same properties. However, vermiculite has a higher water absorption capacity than perlite. Nanobubbles are bubbles with 1-100 nm that can live more stably in water. This study aims to influence the type of media and the addition of Nanobubbles O2 on the growth of Dendrobium burana Green × Ong Ang Ai Boon orchid plantlets. This research was carried out from November to December 2022 at the PT. Java Indo Arjuna Singosari, Malang. This study used a completely randomized design (CRD) with 10 treatments, namely solid MS, gaviota solid, thin liquid film, thin liquid film + NBs O2, vermiculite, vermiculite + NBs O2, perlite, perlite + NBs O2, vermiculite + Perlite, vermiculite + perlite + NBs O2 with 4 replications. The data were analyzed descriptively and the Manova test. The results showed that the vermiculite + NBs O2 treatment had the potential to increase the length of plantlets by 13.80 mm, the wet weight of plantlets by 0.30 g, the percentage of live plantlets by 100% whereas in the vermiculite + perlite treatment has the potential for the first root growth to appear, namely 5 HST. The vermiculite treatment had the potential to increase the highest number of leaves by 5 leaves, whereas in the leaf color treatment the solid MS treatment had a more intense green color.